10-8(x-6)=2-4x

Simple and best practice solution for 10-8(x-6)=2-4x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 10-8(x-6)=2-4x equation:


Simplifying
10 + -8(x + -6) = 2 + -4x

Reorder the terms:
10 + -8(-6 + x) = 2 + -4x
10 + (-6 * -8 + x * -8) = 2 + -4x
10 + (48 + -8x) = 2 + -4x

Combine like terms: 10 + 48 = 58
58 + -8x = 2 + -4x

Solving
58 + -8x = 2 + -4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '4x' to each side of the equation.
58 + -8x + 4x = 2 + -4x + 4x

Combine like terms: -8x + 4x = -4x
58 + -4x = 2 + -4x + 4x

Combine like terms: -4x + 4x = 0
58 + -4x = 2 + 0
58 + -4x = 2

Add '-58' to each side of the equation.
58 + -58 + -4x = 2 + -58

Combine like terms: 58 + -58 = 0
0 + -4x = 2 + -58
-4x = 2 + -58

Combine like terms: 2 + -58 = -56
-4x = -56

Divide each side by '-4'.
x = 14

Simplifying
x = 14

See similar equations:

| 3(16)-4y= | | 32=(g*7)-(g*3) | | GivenA= | | 20(10-x)-200(9-x)=2000 | | 25z^2=1 | | 5/6r-1/3r | | -5x-6x=-5+3 | | 45+4*12=61+4*12 | | 4y-6=3y+25 | | 3m^2+72=33m | | -6(-7x-1)=-8x+9(-3x-4) | | 13-8x+1139=0 | | x^2+49=6 | | 2(1+7x)-3(x-3)=+55 | | 2x+5=-75+8x | | 2x+5=20-x | | -18-9m=m^2 | | 6x+22=14x-17 | | 1/3-40.90 | | 5x+30=10x+40 | | 40.90-1/3 | | 13x^2+11x-24=0 | | -7(8k-4)-7(k-6)=7 | | -7(8k-4)-7(k-6)= | | 3x+1/2-x=6x-4/7 | | y+3=-1/5(x-6) | | -4x+4x=11-4-2-5 | | x+4/3y=-5 | | 289=256x^2+81x^2 | | r^2-7r=8 | | 6.8(x-1)=-0.2x+42.2 | | (30x^3)=0 |

Equations solver categories